Distribution of drought events and their impact on child malnutrition in Senegal [Abstract only] - Jampani, Mahesh; Sambou, Mame Henriette Astou; Alahacoon, Niranga; Amarnath, Giriraj (2023)
Climate change has become a significant threat to Western African countries in recent decades, including Senegal. Further, there has been an increasing occurrence of extreme events such as droughts. Droughts, directly and indirectly, have detrimental impacts on human health and often trigger nutritional status in the respective region. Children under the age of five are more vulnerable to Droughts in terms of malnutrition. In Senegal also, drought has unforeseen impacts on health systems and impacts the nutritional dynamics of children. Besides, There has been limited understanding of how drought occurrence and frequency will influence the nutritional status of children in Senegal. In this context, we looked at spatial and temporal patterns of drought conditions in relation to nutritional status to understand, examine and explore the stunting and wasting cases and undernutrition status in children under five years of age. We analyzed all the provinces of Senegal using satellite-based datasets and drought indices in combination with demographic health surveys (USAID DHS) and Senegalese national health survey datasets. The DHS datasets are yearly based and used to evaluate the long-term patterns, whereas Senegalese government data is monthly and used to evaluate any seasonal dynamics. We employed integrated statistical methods, including factor analysis, spatial autocorrelation, bivariate maps and cross-correlation, to draw the interrelationships and spatiotemporal patterns. The research results convey that there is a significant spatial and temporal relationship between drought and underweight. Further, a significant correlation exists between stunting and wasting cases of children with drought events in the following years. Overall, our research will provide an improved understanding of the vulnerability of children’s health associated with drought events and can help local stakeholders and policymakers to understand the malnutritional status with respect to climate change in Senegal and to develop appropriate policy interventions.